Mengurai Dilema Bioetika dan Syariah atas Daging Tanpa Penyembelihan dalam Kultur Sel Hewan - Rifqi Ilham; Tatang Hernawan; Romli Romli; Tri Cahyanto (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study examines the bioethical and Sharia dilemmas arising from the production of slaughter-free meat through animal cell culture as a modern food innovation. Concerns regarding the halal status of the cell source, the use of culture media such as Foetal Bovine Serum, and ethical issues related to animal welfare necessitate an in-depth analysis of the halal status and moral implications of this technology. The research method employs a literature study with a descriptive qualitative approach, reviewing journals, books, and contemporary fatwas related to cultured meat, bioethics, and Islamic law. The results indicate that the Sharia aspect heavily depends on the cell source, the medium used, and the culture process, while the bioethical perspective highlights animal welfare, scientific transparency, and the moral responsibility of researchers. Furthermore, the acceptance among Muslim communities is significantly influenced by trust in halal certification bodies and the availability of transparent information. This study affirms the need for biotechnology-based halal standardization and the development of fully halal media and supporting materials to ensure the widespread acceptance of cultured meat in the future.